Use of more than one electronic medical record system within a single health care organization - Payne, T.; Fellner, J.; Dugowson, C.; Liebovitz, D.; Fletcher, G. (Applied Clinical Informatics, 2012)
Healthcare organizations vary in the number of electronic medical record (EMR) systems they use. Some use a single EMR for nearly all care they provide, while others use EMRs from more than one vendor. These strategies create a mixture of advantages, risks and costs. Based on our experience in two organizations over a decade, we analyzed use of more than one EMR within our two health care organizations to identify advantages, risks and costs that use of more than one EMR presents. We identified the data and functionality types that pose the greatest challenge to patient safety and efficiency. We present a model to classify patterns of use of more than one EMR within a single healthcare organization, and identified the most important 28 data types and 4 areas of functionality that in our experience present special challenges and safety risks with use of more than one EMR within a single healthcare organization. The use of more than one EMR in a single organization may be the chosen approach for many reasons, but in our organizations the limitations of this approach have also become clear. Those who use and support EMRs realize that to safely and efficiently use more than one EMR, a considerable amount of IT work is necessary. Thorough understanding of the challenges in using more than one EMR is an important prerequisite to minimizing the risks of using more than one EMR to care for patients in a single healthcare organization.Citation: Payne T, Fellner J, Dugowson C, Liebovitz D, Fletcher G. Use of more than one electronic medical record system within a single health care organization. Appl Clin Inf 2012; 3: 462–474http://dx.doi.org/10.4338/ACI-2012-10-RA-0040
Keywords: Electronic health records; medical records systems; computerized